[Sutherland, Margaret (composer) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Margaret Ada Sutherland AO OBE (20 November 1897 - 12 August 1984) was an Australian composer. The University of Melbourne conferred an honorary doctorate of music on Margaret Sutherland in 1969, and she was appointed an Officer of the Order of the British Empire (OBE) in 1970. She was awarded the Queen Elizabeth II Silver Jubilee Medal in 1977, and was appointed an Officer of the Order of Australia in the 1981 Queen's Birthday Honours.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Sutherland, M. -- 1897-1984 -- Miscellanea; Composers -- Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian